Studying Programming in the Neuroage: Just a Crazy Idea? Programming research has entered the Neuroage. - Siegmund, Janet; Peitek, Norman; Brechmann, André; Parnin, Chris; Apel, Sven (Communications of the ACM, 2020)
The article focuses on program comprehension research. Whether neuroimaging is the answer to better understand the cognitive processes of programmers as they read and understand code is considered. The authors also discuss their first program comprehension study conducted with students, using a functional magnetic resonance imaging (fMRI) scanner, and mention topics including the brain's left hemisphere and cognitive load.